2018
DOI: 10.1130/ges01680.1
|View full text |Cite
|
Sign up to set email alerts
|

Establishing chronologies for alluvial-fan sequences with analysis of high-resolution topographic data: San Luis Valley, Colorado, USA

Abstract: On active alluvial fans, debris-flow deposits and frequent avulsions produce a rough topographic surface. As is the case in many initially rough landforms produced by catastrophic processes, the topography of alluvial fans is progressively smoothed, producing textural differences useful in establishing relative age criteria for fans. Here, we outline an approach for defining a quantitative, numerical chronology for the surfaces of alluvial fans from topographic analysis, although the method is generalizable to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 53 publications
1
4
0
Order By: Relevance
“…Ages from seven separate clasts from the ZP site, previously reported by Johnstone et al. (2018), yielded similar ages ranging from 19.8 ± 0.1 to 26.2 ± 1.2 ka. Clustering of dates suggests that carbonate at this site formed during a period of ∼6 kyrs.…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…Ages from seven separate clasts from the ZP site, previously reported by Johnstone et al. (2018), yielded similar ages ranging from 19.8 ± 0.1 to 26.2 ± 1.2 ka. Clustering of dates suggests that carbonate at this site formed during a period of ∼6 kyrs.…”
Section: Resultssupporting
confidence: 75%
“…Dense, crystalline carbonate was also targeted specifically to minimize the incorporation of dust-size detrital carbonate and silicate material in the authigenic soil carbonate, in order to reduce their contribution to the measured carbon, oxygen, and U-series isotope ratios used for paleoenvironmental reconstruction and geochronology. Previous studies showed that soil carbonates sampled this way in the SLV are relatively low in detritus component, evidenced by successful U-series dating with low detrital 232 Th for many of the exact samples used in this study (Johnstone et al, 2018;Ruleman et al, 2019). Specific depths for each sample zone were not carefully recorded.…”
Section: Field and Laboratory Samplingmentioning
confidence: 92%
See 1 more Smart Citation
“…Features of alpine glacial erosion and deposition are abundant in many valleys. Valley mouths have subsequently been deeply incised by streams in response to ongoing tectonism and are fronted by well-developed alluvial fans with surfaces indicating multiple stages of development [25,26].…”
Section: Geologic and Geomorphic Settingmentioning
confidence: 99%
“…In recent decades, digital elevation models (DEMs) derived from airborne laser scanning (ALS) have been widely used for studies of Earth surface processes [14,15], and references therein]. DEMs proved to be an invaluable tool in geomorphological and natural hazards mapping, identifying geomorphological processes, detecting small-scale features, monitoring surface changes, reconstructing landscape evolution, re-evaluating the existing maps, and even determining surface age [16][17][18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%